Hematological, physiological and biochemical effects-induced in female albino rats after chronic administration of Cinnamomum camphora oil - Dr, Mohamed; Massry, El; A., A. (JOURNAL OF ADVANCES IN BIOLOGY, 2014)
This present study was aimed to investigate hematological and physiological effects of different concentrations of camphor oil on selected organs of female albino rats. Camphor oil at doses of 400, 500 and 600 Î¼l/kg body weight/day was administered intraperitoneally for 28 days. The obtained data revealed significant decrease in RBC, s, Hb, Hct and PLT in camphor oil treated rats. The prominent features of WBC,s, after the camphor oil treatment, were leucopenia, neurtophilia, monocytosis and lymphopenia. However, the camphor oil had no significant effect (P<0.05) on MCH, MCHC, MCV and RDW when compared with controls. The activities of diagnostic marker enzymes, including AST and ALT plasma levels were markedly increased in camphor oil treated rats. Daily intraperitoneal treatment with camphor oil resulted in significant (P<0.05) increment in plasma urea, creatinine and without any differences in total proteins. Total lipid, triglycerides, total cholesterol, LDL- cholesterol, VLDL-cholesterol and HDL-cholesterol were decreased in treating rats as compared to the control group. All the treated groups showed an increase in FSH, LH, progesterone and estrogen concentrations. Furthermore, the different doses of camphor oil caused a decrease in PRL concentration. Body weight and organ/body weight ratios were significantly increased after camphor oil treatments.The present results show that camphor oil has adverse health effects and consequently camphor remains a product with the potential for serious toxicity